How do patient feedback systems work in low-income and middle-income countries? Insights from a realist evaluation in Bangladesh. Issue 2 (10th February 2021) - Mirzoev, Tolib; Kane, Sumit; Al Azdi, Zunayed; Ebenso, Bassey; Chowdhury, Ayesha Afroz; Huque, Rumana
Abstract : Background: Well-functioning patient feedback systems can contribute to improved quality of healthcare and systems accountability. We used realist evaluation to examine patient feedback systems at health facilities in Bangladesh, informed by theories of citizenship and principal–agent relationships. Methods: We collected and analysed data in two stages, using: document review; secondary analysis of data from publicly available web-portals; in-depth interviews with patients, health workers and managers; non-participant observations of feedback environments; and stakeholder workshops. Stage 1 focused on identifying and articulating the initial programme theory (PT) of patient feedback systems. In stage 2, we iteratively tested and refined this initial theory, through analysing data and grounding emerging findings within substantive theories and empirical literature, to arrive at a refined PT. Results: Multiple patient feedback systems operate in Bangladesh, essentially comprising stages of collection, analysis and actions on feedback. Key contextual enablers include political commitment to accountability, whereas key constraints include limited patient awareness of feedback channels, lack of guidelines and documented processes, local political dynamics and priorities, institutional hierarchies and accountability relationships. Findings highlight that relational trust may be important for many people to exercise citizenship and providing feedback, and that appropriate policy and regulatory frameworks with clear lines of accountability are critical for ensuring effective patient feedback management within frontline healthcare facilities. Conclusion: Theories of citizenship and principal–agent relationships can help understand how feedback systems work through spotlighting the citizenship identity and agency, shared or competing interests, and information asymmetries. We extend the understanding of these theories by highlighting how patients, health workers and managers act as both principals and agents, and how information asymmetry and possible agency loss can be addressed. We highlight the importance of awareness raising and non-threatening environment to provide feedback, adequate support to staff to document and analyse feedback and timely actions on the information.